1998
DOI: 10.1002/(sici)1521-3803(199804)42:02<89::aid-food89>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

African yam bean hull chemical composition and its effects on rat′s mineral retention, serum biochemical components and enzymatic activities

Abstract: The influence of yam bean hull on rat's mineral metabolism, serum composition and enzymatic activities was investigated. The chemical composition of the bean's hull shows a reasonably high crude protein (11.4%) but very low contents of crude fat (2.6%), phytic acid (82 mg/100 g) and phytin-phosphorus (23 mg/100 g). K and Ca are the major minerals present in yam bean hull. The hull, rich in cell wall polysaccharides, is composed of cellulose (35.4%), non-cellulose fractions made of pectin and hemicellulose put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Em experimentos de 24 dias de duração e mantendo constante o conteúdo de fitato pela adição de fitato de sódio, pães contendo níveis diferenciados de fibra alimentar (branco, marron e integral), não interferiram na absorção de cálcio, zinco e ferro, sugerindo que a fibra, em si, não influenciou a absorção destes minerais (Andersson et al, 1983). Agunbiade & Longe (1998) demonstraram , em ratos, que a casca de um feijão cultivado na África, rica principalmente em potássio e cálcio, causou a diminuição da absorção de minerais, exceto o cálcio. Essa casca era constituída de 354 g kg -1 de celulose, 419 g kg -1 de hemicelulose + pectina, 36 g kg -1 de lignina, bem como quantidades de 114 g kg -1 de proteína bruta, 26 g kg -1 de lipídeo, 0,82 g kg -1 de ácido fítico e 0,23 g kg -1 de fósforo-fitina.…”
Section: Introductionunclassified
“…Em experimentos de 24 dias de duração e mantendo constante o conteúdo de fitato pela adição de fitato de sódio, pães contendo níveis diferenciados de fibra alimentar (branco, marron e integral), não interferiram na absorção de cálcio, zinco e ferro, sugerindo que a fibra, em si, não influenciou a absorção destes minerais (Andersson et al, 1983). Agunbiade & Longe (1998) demonstraram , em ratos, que a casca de um feijão cultivado na África, rica principalmente em potássio e cálcio, causou a diminuição da absorção de minerais, exceto o cálcio. Essa casca era constituída de 354 g kg -1 de celulose, 419 g kg -1 de hemicelulose + pectina, 36 g kg -1 de lignina, bem como quantidades de 114 g kg -1 de proteína bruta, 26 g kg -1 de lipídeo, 0,82 g kg -1 de ácido fítico e 0,23 g kg -1 de fósforo-fitina.…”
Section: Introductionunclassified
“…This did not result in any pathological changes in liver or kidneys and did not substantially influence protein metabolism parameters such as protein, albumin, BUN and creatinine. Also high, a 15% pure cellulose additive in diet did not influence the total protein level and its fractions in the blood serum of rats (AGUNBIADE & LONGE 1998). An experiment by CAO et al (2003) revealed that the pure cellulose content in the diet of Single Comb White Leghorn chickens should not exceed 3.5%.…”
Section: Resultsmentioning
confidence: 89%
“…These include an increase in the weight of individual segments of the digestive tract, gizzard activity, pancreatic enzyme activity and a higher concentration of bile acids in jejunum, positive changes in the morphology of the small intestine mucosa resulting in a larger absorption surface. It is wellknown that dietary fibre has the ability to precipitate minerals in the digestive content which decreases their absorption (VAN DER AAR 1983;AGUNBIADE & LONGE 1998;GREGER 1999;SMULIKOWSKA 2002). In view of the studies mentioned above, it seems justified to ask whether cellulose, as the major component of insoluble fibre fraction (considering its physico-chemical properties), can affect the protein profile and mineral concentration in the blood of broiler chickens.…”
mentioning
confidence: 99%
“…Incorporating AYB in the feeds of some livestock has been attempted by [5] [6]. It can be used in inclusion or as a substitute for protein source in livestock feed provided other food crops used in livestock feed is available to supplement the AYB content for increased feed consumption and palatability [7].…”
Section: Introductionmentioning
confidence: 99%